Managerial competencies and small business venture performance: an emerging economies perspective - Isichei Ejikeme Emmanuel; Rimamnde Rikwentishe; Igbatigbi Friday Attayi (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — The challenges faced by most small-scale ventures in developing economies has largely been attributed to not just the environment issues, but also the poor human capacity of most managers to effectively make decisions that will ensure the continued survival of the business over a period. The objective of this research was thus to assess the effect of managerial competency on performance of SMEs.Method — We adopted descriptive survey research design for this study. We used a sample of 394 SMEs managers for the survey, which were selected using convenience sampling technique. This research relied on content validity and internal consistency measure for validity and reliability respectively. We used multiple regression with the aid of SPSSv23 for data analysis. Result — The outcome shows that managerial competencies affect the performance of small-scale enterprises. Also, we found that interpersonal competency of manager of SMEs is low, while the cognitive competency made the strongest unique contribution to explain venture performance. We conclude that to drive improved performance there must be effort targeted towards improving the skills of managers of SMEs in the country.Contribution — This research validates the resource-based view theory and contributes to expand literature on competency and leadership from an emerging economies context.